DINAMIKA KONFLIK KEPENTINGAN PEMERINTAH KABUPATEN KAMPAR DAN PEMERINTAH KABUPATEN ROKAN HULU DALAM MEMPEREBUTKAN STATUS LIMA DESA DI PERBATASAN - Era Refani; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Local proliferation after Reformasi not only brought good impact on the implementation of an autonomous regional government, but also brought bad impact that generally caused by vary things, one of them is because unclear in requiring in doing in regional expansion. In case of local proliferation, so the borderland is being crusial issue that often being dispute subject between two local governments.Conflict has happened between Pemkab Kampar and Pemkab Rokan hulu in struggling five villages status after proliferation with UU Number 53 Year 1999. The five villages are Desa Muara Intan, Intan jaya, Tanah Datar, Rimba Jaya, and Rimba Makmur.The purpose of this research is to know how The Interest Conflict Dynamics Regency Government of Kampar and Regency Government of Rokan Hulu in Struggling Five Villages Status in Borderland and its settlement. The approach of this research is qualitative approach and the type of this research is descriptive.This research’s result is showing that first, UU Number 53 Year 1999 has a weakness because the border was determined without region border in points so it will be definitive and two local government interpret UU Nomor 53 Tahun 1999 and they are entitled to these five villages. Second, Pemprov Riau has facilitated the settlement and has handed it it to the Mendagri. For The implementation of public service in five villages is carried out by the Pemkab in accordance with Permendagri Number 137 Year 2017. Keywords: Proliferation, interests, border